Responses of retinal and brain microvasculature to streptozotocin induced diabetes revealed by global expression profiling - Li, Youhai; Faiz, Alen; Moshage, Han; Schilling, Lothar; Kamps, Jan AAM (Diabetes & vascular disease research, 2023)
This study aims to determine the effects of diabetes in the retinal and brain microvasculature through gene expression profiling. Twelve male Wistar rats were randomly divided into two groups: streptozotocin-induced diabetic rats and time-matched nondiabetic rats. The retinal microvessels (RMVs) and brain microvessels (BMVs) were mechanically isolated from individual rats. Differentially expressed genes (DEGs) in diabetic and nondiabetic microvessels were identified by cDNA microarrays analysis. In RMVs, we identified 43 DEGs, of which 20 were upregulated while 23 were downregulated by diabetes. In BMVs, 35 genes DEGs were identified, of which 22 were upregulated and 13 were downregulated by diabetes. Altered expression of the Nars, Gars, Mars, Iars, Yars, Bcl2, Nqo1, NR4A3, Gpd1, Stc1, Tsc22d3, Tnfrsf21 mRNA as observed in the microarray analyses, was confirmed by quantitative RT-PCR. The aminoacyl-tRNA synthetases (aaRSs) pathway in RMVs was significantly overrepresented as compared to BMVs. Our study demonstrates for the first time that in the brain microvasculature multiple compensatory mechanisms exists, serving to protect brain tissue from diabetic insults, whereas these mechanisms are not activated in the retinal microvasculature. This provides new insights as to why brain microvasculature is less susceptible to diabetes.
Online veröffentlicht: 6. Januar 2023
Gesehen am 30.09.2024